Ecologically unequal exchange and uneven development patterns along global value chains - Jeff Althouse; Bruno Carballa Smichowski; Louison Cahen-Fourot; Cédric Durand; Steven Knauss (Roskilde University, Department of Social Sciences and Business, Socio-Economic Research Centre (SECO), 2022)
The ecologically unequal exchange (EUE) literature has provided ample empirical evidence for asymmetric transfer of material and energy resources from low-income to high-income countries. However, research has not been able to clearly specify the causal mechanisms driving these processes. This paper relates participation in global value chains (GVCs) to development patterns and ecologically unequal exchange. We conduct a principal components analysis and a clustering analysis along six dimensions (GVC participation, GVC value capture, investment, socioeconomic development, domestic environmental impact and international environmental balance) for 133 countries between 1995 and 2015. We find three social, ecological, productive development and GVC insertion patterns: "curse of GVC marginalization", "ecologically perverse upgrading" and "reproduction of the core". While our results confirm the asymmetry in ecological degradation between high-income and low-income economies shown by EUE, they support the existence of alternative mechanisms to account for it. We argue that environmental asymmetries are driven mostly by differences in how countries articulate within GVCs, and therefore cannot be ascribed to relations of ecologically unequal exchange, alone. Countries with a higher capacity to capture value from GVC participation ("reproduction of the core") are able to displace environmental impacts to countries facing a trade-off between the positive socioeconomic impacts of rapid GVC integration and ecological degradation ("ecologically perverse upgrading"). GVC marginalization, in turn, constitutes a barrier to socio-economic benefits and to imported ecological degradation. However, the lack of diffusion of more ecologically efficient processes through GVCs has a negative impact on domestic ecological degradation for countries of the "curse of GVC marginalization" group.
Keywords: 330